Hydrothermal Synthesis of TiO2/Al2O3 Nanocomposite and its Application as Improved Sonocatalyst - Ali S. Ali, Assist. Prof.; J. Mohammed, Alaa; R. Saud, Haider (International Journal of Engineering and Technology, 2018)
The powder of TiO2/Î±-Al2O3 nanocomposite for Sonocatalysis decolorisation was successfully achieved in the Hydrothermal autoclave reaction for 6 hours and completely crystallized into Anatase phase at temperature of 220oC which more lower than normal required calcination temperature 500oC. The TiO2/Î±-Al2O3 nanoparticles examined using FT-IR, SEM, TGA, X-ray diffraction studies( XRD), The results indicate the formation of nanocomposite with tetragonal Anatase phase and average crystal size of 21.4nm for TiO2/Î±-Al2O3 while the average crystal size of 8.1nm for Al2O3, which are calculated according to Scherrerâ€™s equation. This powder was mixed with methylene blue to study the effect of nanocomposite on it, the prepared nanocomposite show highly decolorisation percentage of methylene blue solution.Â